First-principles calculations of ferroelectricity and structural stability in Bi- and Alkali-Metal-Modified BaTiO3 for PTC thermistor applications - Sittichain Pramchu (2018)
© 2018 Elsevier Ltd and Techna Group S.r.l. First-principles density functional theory (DFT) was used to seek the possibility of enhancing ferroelectricity, structural stability, and TC of BaTiO3 by Bi/alkali-metals co-doping. From the results, among M = Li, Na, K, Rb, and Cs, we found that K gives the largest c/a ratio (tetragonality) and spontaneous polarization (Ps), which these c/a and Ps are also larger than those from pure BaTiO3. In addition, the calculated solution energy (at Ba-poor condition) reveals that the incorporation of Bi and K on A site yields the most stable structure. The predicted enhancements of ferroelectricity and structural stability in the case of Bi/K modified BaTiO3 is found to be weakly dependent on how Bi and K are arranged to occupy different positions of A site in the supercell. Consequently, our results suggest that K is the best candidate. The findings can then be used to suggest ways of enhancing ferroelectricity, structural stability, and TC in BaTiO3 ceramics for broadening the operating temperature of BT-based PTC thermistor.